2018
DOI: 10.1177/1545968318804425
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation to Enhance Functional Recovery After Stroke: Studies in Animal Models

Abstract: Background. Stroke is the leading cause of adult disability, but treatment options remain limited, leaving most patients with incomplete recovery. Patient and animal studies have shown potential of noninvasive brain stimulation (NIBS) strategies to improve function after stroke. However, mechanisms underlying therapeutic effects of NIBS are unclear and there is no consensus on which NIBS protocols are most effective. Objective. Provide a review of articles that assessed effects and mechanisms of repetitive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 89 publications
(187 reference statements)
0
26
0
1
Order By: Relevance
“…Cathodic (−) tDCS has also been shown to reduce edema, inflammation, cell apoptosis, and cortical glutamate, creatine, and taurine levels. Cathodic (−) tDCS also preserves cell structure within the cerebral cortex which can lead to reduction in infarct volume and better recovery of function [ 64 ]. Other theories of cerebral interactions during the recovery from exercise suggest that the cerebral hemispheres work in cooperation rather than competition.…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…Cathodic (−) tDCS has also been shown to reduce edema, inflammation, cell apoptosis, and cortical glutamate, creatine, and taurine levels. Cathodic (−) tDCS also preserves cell structure within the cerebral cortex which can lead to reduction in infarct volume and better recovery of function [ 64 ]. Other theories of cerebral interactions during the recovery from exercise suggest that the cerebral hemispheres work in cooperation rather than competition.…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…III. Recovery: rTMS has a positive impact on functional recovery, such as limb motor recovery in stroke patients; however, optimal rTMS parameters and high-quality evidence require further research (Pollock et al, 2014;Boonzaier et al, 2018;Yang et al, 2018;Xiang et al, 2019). IV.…”
Section: Abstract As Indicators Of Emerging Trendsmentioning
confidence: 99%
“…rTMS is the most widely used non-invasive brain stimulation technique currently available (George and Aston-Jones, 2010;Miniussi et al, 2013;Cirillo et al, 2017;Lowe et al, 2017;Lucena et al, 2019). Numerous studies have investigated the effects and mechanisms underlying various rTMS protocols, which remain incompletely understood (Fitzgerald et al, 2006b;Boonzaier et al, 2018;Zorzo et al, 2019). Low-frequency (≤1.0 Hz) rTMS usually reduces cortical excitability, whereas high-frequency (>1.0 Hz) rTMS (HF-rTMS) raises excitability (Maeda et al, 2000;Rossini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on epidural cortical stimulation (CS), in which electrodes are neurosurgically placed on the surface of the brain for stimulation; and noninvasive brain stimulation (NIBS) techniques, which included transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS). Recent years have seen enthusiastic research activity on stroke treatment using brain stimulation in both humans and laboratory animals with promising results [46][47][48]. Animal experiments are slowly revealing the effects of brain stimulation at the cellular level (Figure 1), and studies have reported the effects of combining these techniques with cell therapy.…”
Section: Brain Stimulation For Stroke Recoverymentioning
confidence: 99%